Dampak Alih Fungsi Lahan Sawah Petani Pemilik terhadap Kehidupan Rumah Tangganya (Studi Kasus di Subak Lange, di Kawasan Desa Pemecutan Kelod, Kecamatan Denpasar Barat) - WIRARAJA, I GUSTI JAYA; WINDIA, I WAYAN; SUDARTA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.2, April 2016, 2016)
Abstract The Impact of Land Conversion Paddy Farmer Owners To Home Life (A Case Study in Subak Lange, in the Area South Pemecutan Village, West Denpasar District) The Land Conversion Paddy Farmer Owners To Home Life have an impact on the decline in agricultural production and will have an impact on changes in the orientation of economic, social, cultural, political, and community. Increasing land use for shelter, a place to do business, the fulfillment of public access and other amenities that will lead to the available land so that the land was converted narrowing. The purpose of this study was to determine the impact of conversion land use on the lives of farmers. How the lives of the farmers after selling his farm land. This study using in-depth interview technique. This study using variables and indicators in the three states of culture, namely: mindset, social systems, and artifacts or objects. Subak Lange is in the Pemecutan Village, West Denpasar District. Subak Lange is a located in the area South Pemecutan Village. West Denpasar Ditstrict. This study was conducted by purposive, there are some reason for location selection. The result of the study showed that land conversion have an impact on a better life than before, and some result showed there is also a feeling of life is not better after seling their farm land. This can be measured   in three states, namely culture mindset, social systems, and artifacts or objects. The purpose of selling his farm land because farmers used to open a business, health cost, home renovation cost, religious ceremonies, and used to dissipate. The reasons to sell farm land due to high taxes and harvest is uncertain. The feeling after selling the farm land, some farmer are happy anda some farmer feels regret. The interaction of the public prominence and families, some are good and some are not good or there is also have a conflict. The farmer’s income after selling their farm land more better than be a farmer by profession before. It needs good preparation from the farmers to the use of proceeds from the sale of rice fields used for working capital that is useful to farmers a better life because of farm land are sold out.
Keywords: The Impact; Land Conversion; Domestic Life of Farmers; Subak